Variation of arsenic in shallow aquifers of the Bengal Basin: Controlling geochemical processes - Kundu, A.; Biswas, A.; Bhowmick, S.; Chatterjee, D.; Mukherjee, Abhijit; Neidhardt, H.; Berner, Z.; Bhattacharya, P. (2016)
© 2016 Taylor & Francis Group, London. The natural occurrence of high dissolved Arsenic (As) in groundwater is quiet common and has been reported from almost entire globe. Nevertheless the scale of problem is most severe in several countries of South and South East Asia, notably in BDP (Bengal Delta Plain). Different As release mechanism has been put forward to explain As enrichment in groundwater. The groundwater As distribution and their relationship with land-use pattern suggest that As release is influenced by local conditions (e.g. sanitation, presence of surface water, agricultural practice). High rate of groundwater withdrawl can accelerate As mobilization by enhancing the transport of degradable organic matter with recharge water from the surface.